Residual selenate and selenite in the soil: Effect on the accumulation of selenium, macronutrients, and gas exchange in arugula - Siueia Júnior, Matias; da Silva, Deivisson Ferreira; Cipriano, Patriciani Estela; de Souza, Ray Rodrigues; Faquin, Valdemar; Silva, Maria Ligia de Souza; Guilherme, Luiz Roberto Guimarães (Scientia horticulturae, 2024)
•Residual Se from the selenate source has enhanced the plant's photosynthetic system.•Selenite residue did not supply sufficient residual Se for arugula to absorb.•Se residual from the previous crop, a key player, enhances gas exchange in arugula.•Selenate increased Se export, leading to higher fresh mass in arugula. Residual selenate and selenite in the soil can influence selenium (Se) content, macronutrients accumulation, and gas exchange in arugula. This study explored the impact of Se absorption by plants and their growth when previously exposed to selenium. Absorption of macronutrients, micronutrients, and physiological parameters of arugula plants (Eruca sativa), as well as residual Se uptake, were assessed following Se addition as sodium selenate (Na2SeO4) and sodium selenite (Na2SeO3) to the soil in the previous crop. The research was conducted under greenhouse conditions, with a completely randomized design in a 2 × 3 + 1 arrangement, with two Se sources (sodium selenate - Na2SeO4 and sodium selenite - Na2SeO3) applied at three Se doses (0.6, 1.2, and 1.8 mg dm−3) via soil and a control, without Se application, with three replications. The results indicated that applying 0.6 Se mg dm−3 as selenite did not significantly contribute to the arugula's uptake of residual selenium. On the other hand, arugula exhibited higher dry mass production and macronutrient accumulation content in the shoots due to increased physiological processes such as photosynthetic rate, transpiration, and instantaneous carboxylation efficiency and stomatal conductance when it absorbed the residual Se in the form of selenate at the increasing doses. This study underscores the need for further comprehensive studies of residual Se in the soil to comprehend its dynamics and relationship with plant absorption, highlighting the potential implications of this research in soil science and agricultural practices.